1983
DOI: 10.1210/endo-112-6-2206
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Corticotropin Releasing Factor-Like Immunoreactivity in Mammalian Hypothalamic and Extrahypothalamic Brain Tissue as Determined With a Monoclonal Antibody to the Ovine Material.

Abstract: A monoclonal antibody to ovine corticotropin releasing factor (CRF) has been produced by fusion of a non-producing plasmacytoma cell line P3U1 with spleen cells of Balb/c mice immunized with the synthetic 41 amino acid peptide coupled covalently with rabbit myosin by a heterobifunctional reagent, N-succinimidyl 3-(2-pyridyldithio) propionate. A total immunizing dose of 500 micrograms resulted in a highly specific, high-affinity antibody with a Ka of 0.15 x 10(12) M-1, which was used to establish a specific RIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…It was prepared by the same methods used previously to raise antiserum for a highly sensitive radioimmunoassay for CRF (22,23). As confirmed by logit-log transformations of the data and statistical comparisons of the resultant regression lines, this antiserum to oCRF displayed parallelism to extracts of guinea pig hypothalamus and extra-hypothalamic brain tissue (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…It was prepared by the same methods used previously to raise antiserum for a highly sensitive radioimmunoassay for CRF (22,23). As confirmed by logit-log transformations of the data and statistical comparisons of the resultant regression lines, this antiserum to oCRF displayed parallelism to extracts of guinea pig hypothalamus and extra-hypothalamic brain tissue (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…This indicates the possibility of a particularly antigenic region at the C terminus, in agreement with the suggestion from structural prediction studies for ovine CRF-41 (Pallai, Mabilia, Goodman et al 1983) that hydrophilic residues 33, 34, 36 and 37 are likely to be involved in antigenic sites. Another murine mono¬ clonal antibody raised against ovine CRF-41 (Hollander, Audhya, Russo et al 1983) was reported to be able to bind ovine CRF-41 and sauvagine and was used to detect immunoreactivity in ovine, bovine and murine tissue, suggesting that this antibody also recognized a region of CRF-41 with cross-species homology. Biological characterization of the antibodies KCHMB001 and KCHMB003 showed that they neutralized the ACTH-releasing activity of rat CRF-41 in a pituitary bioassay in a manner similar to the monoclonal described by Van Oers et al (1989).…”
Section: Discussionmentioning
confidence: 99%
“…Sections of the L6/S1 spinal cord, brainstem, and hypothalamus were immunostained with two different antibodies that were generated in rabbits against CRF (Hollander et al, 1983; Silverman et al, 1989; 1:1,500 and 1:1,000 dilution, respectively; gifts from Dr. Ann‐Judith Silverman, Columbia University, and Dr. Wylie Vale, The Salk Institute). Sections were incubated in the primary antibody for 48 hr, washed in 0.01 M phosphate‐buffered saline (PBS), and incubated for 80 min in goat anti‐rabbit IgG conjugated to Alexa 594 or Alexa 488 (Molecular Probes, Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%